Immunohistochemical Assessment of HER3 Expression in Pancreatic Cancer - Hosnie Hoseini; Azade Sarani (Krupanidhi College of Pharmacy, 2024)
Pancreatic cancer (PC) is one of the most lethal tumor malignancies, which has a poor prognosis and can be the cause of death despite tumor removal. New molecular investigations for therapeutic purposes have shown the expression of HER3 in pancreatic adenocarcinoma. Family receptors HER3 play an effective role in malignancies such as lung and colon cancer. The aim of this study is to investigate the expression of HER3 in pancreatic cancer samples and the relationship between the expression of the receptor HER3 and the clinical complications of patients. Samples were taken from 75 patients with pancreatic cancer and subjected to immunohistochemical staining to evaluate the expression. Based on the intensity of staining, scores were assigned to each sample for HER3 receptor. Scores of +2 or +3 were defined as positive staining. The obtained data were analyzed using SPSS 16 software and Chi-square tests. P<0.05 was considered statistically significant. The results showed the expression of HER3 in normal pancreatic tissue. The expression decreased from the early to late stage (p=0.05). Multivariate survival analysis showed that only stage had independent prognostic value (p=0.015). HER3 expressed in normal pancreatic tissue, but the expression is lost in pancreatic cancer. According to the study, it seems that targeted treatment in pancreatic cancer has no relationship with expression. Keywords EGFR, HER3, Pancreatic adenocarcinoma, Prognosis